Analysis and calculation of magnetic flux density distribution and core loss of nanocrystalline transformer - Zhenyu Cai; Chuanyang Zha; Ruopu Zhan; Gang Huang (Energy Reports, 2022)
Nanocrystalline transformers have better electromagnetic properties than electrical steel transformers, such as lower losses. Nowadays, numerous nanocrystalline magnetic cores have served in the research work of high-frequency transformers, but there is still a lack of application in low-frequency transformers. It is of guiding significance to research the magnetic flux density distribution and core loss of nanocrystalline transformers under power frequency. This paper carries out a systematic simulation study on the magnetization and loss characteristics of nanocrystalline transformers under different excitations, and analyzes the distribution of magnetic flux density and core loss characteristics.